2001
DOI: 10.1108/eb060736
|View full text |Cite
|
Sign up to set email alerts
|

Economic Value‐Added: A Review of the Theoretical and Empirical Literature

Abstract: With increasing pressure on firms to deliver shareholder value, there has been a renewed emphasis on devising measures of corporate financial performance and incentive compensation plans that encourage managers to increase shareholder wealth. One professedly recent innovation in the field of internal and external performance measurement is a trade‐marked variant of residual income known as economic value‐added (EVA). This paper attempts to provide a synoptic survey of EVA's conceptual underpinnings and the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 30 publications
4
51
0
14
Order By: Relevance
“…Bank's performance measure can be classified into traditional, economic and market-based [2]. For example Stern and Stewart developed a model called Economic Value Added (EVA) which takes into account the opportunity cost for stockholders to hold equity in a bank, measuring whether a company generates an economic rate of return higher than the cost of invested capital in order to increase the market value of the company [59]. There have been a large number of empirical studies on bank performance around the world especially commercial banks but, very little on bank performance has been done in Nigeria.…”
Section: Bank Performancementioning
confidence: 99%
“…Bank's performance measure can be classified into traditional, economic and market-based [2]. For example Stern and Stewart developed a model called Economic Value Added (EVA) which takes into account the opportunity cost for stockholders to hold equity in a bank, measuring whether a company generates an economic rate of return higher than the cost of invested capital in order to increase the market value of the company [59]. There have been a large number of empirical studies on bank performance around the world especially commercial banks but, very little on bank performance has been done in Nigeria.…”
Section: Bank Performancementioning
confidence: 99%
“…After conducting a study on 112 articles on EVA Sharma & Kumar (2010) concluded that it is significantly necessary to conduct research on EVA in order to signify greater empirical certainty of EVA as performance measurement tool as there is mixed evidences on the superiority of the concept. [21] proposed the same. Worthington & West argued that there is an obvious requirement to examine the usefulness of EVA over traditional measures over a longer period of time frame which would allow greater empirical certainty on EVA's status as a corporate performance measure.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Next research on the effects of explanatory power of Economic Value Added (EVA) and traditional measures of the stock return are done by Worthington & West (2001) on 110 Australian companies with the period 1992-1998 using the same method with Biddle, this study found the same results that traditional measurements are more correlated with stock returns than Economic Value Added (EVA) method. Turvey et al (2000) studies on the 17 food processing companies listed on Canadian stock exchanges about the explanatory power of Economic Value Added (EVA) on stock return, this study found that there was no relationship or explanatory power of Economic Value Added (EVA) on stock return.…”
Section: Introductionmentioning
confidence: 82%
“…Researchers using this method because the traditional measurement of accounting like financial ratios, accounting distortions that are not able to measure the added value created in a certain period. In some empirical literature also found not one single financial ratio that could explain changes in shareholder wealth (Worthington & West, 2001).…”
Section: Introductionmentioning
confidence: 99%